Zebrafish (Danio rerio) larva as an in vivo vertebrate model to study renal function - Bolten, Jan Stephan; Pratsinis, Anna; Alter, Claudio Luca; Fricker, Gert; Huwyler, Jörg (American journal of physiology. Renal physiology, 2022)
Download figureDownload PowerPoint
Gesehen am 06.04.2022